Analisis Memahami Pelanggan Dan Pesaing Untuk Meraih Keunggulan Di Sma Pelita Bangsa - Angela Anugrah; Muamar Rizki Zidan; Veta Lidya Delimah Pasaribu (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Rivalry in the education field, especially at SMA Pelita Bangsa, has heightened alongside rising expectations for quality and evolving preferences of students and their parents. Thus, market analysis is essential as a means to comprehend customers—students and parents—and to evaluate the positioning and strategies of rivals within educational institutions. This insight is anticipated to assist the school and its students in obtaining a lasting competitive edge. This research seeks to analyze students' comprehension of customers and competitors while developing strategies that can enhance SMA Pelita Bangsa's standing. The approach employed is qualitative research utilizing a Participatory Action Research (PAR) framework, incorporating observations, Focus Group Discussions (FGD), detailed interviews, and SWOT analysis. The findings indicate that while students grasp the significance of market analysis, its execution is still obstructed by a lack of data and inadequate cooperation among the school, students, and parents. SMA Pelita Bangsa excels in teacher quality and facilities but must improve innovation and data usage. Through differentiation methods and enhanced collaboration with stakeholders, the school and students are equipped to tackle competition successfully and cultivate a more robust entrepreneurial mindset. This research provides essential insights for formulating entrepreneurship strategies and competitive edge in educational environments